2004
DOI: 10.1007/s11103-004-2651-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the S-locus structure in Prunus armeniaca L. Identification ofS-haplotype specific S-RNase and F-box genes

Abstract: The gametophytic self-incompatibility (GSI) system in Rosaceae has been proposed to be controlled by two genes located in the S -locusan S-RNase and a recently described pollen expressed S -haplotype specific F-box gene (SFB). However, in apricot (Prunus armeniaca L.) these genes had not been identified yet. We have sequenced 21 kb in total of the S -locus region in 3 different apricot S -haplotypes. These fragments contain genes homologous to the S-RNase and F-box genes found in other Prunus species, preservi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 56 publications
(123 reference statements)
3
115
0
Order By: Relevance
“…To assess whether or not there is a correlation between S-pistil and Spollen genes that contributes to genetic variability, all published SFB genes found in Prunoideae have been analyzed in this study. A total of 10, 32, 17, 12, and 24 different alleles have been identified in plum, apricot, Japanese apricot, sweet cherry, and almond, respectively (Yamane et al 2003b;Romero et al 2004;Ushijima et al 2004;Vaughan et al 2006;Zhang et al 2007;Wu et al 2009Wu et al , 2013. In contrast, only four S-RNase alleles and four SFB alleles are identified for peach cultivars and their wild relatives in this study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…To assess whether or not there is a correlation between S-pistil and Spollen genes that contributes to genetic variability, all published SFB genes found in Prunoideae have been analyzed in this study. A total of 10, 32, 17, 12, and 24 different alleles have been identified in plum, apricot, Japanese apricot, sweet cherry, and almond, respectively (Yamane et al 2003b;Romero et al 2004;Ushijima et al 2004;Vaughan et al 2006;Zhang et al 2007;Wu et al 2009Wu et al , 2013. In contrast, only four S-RNase alleles and four SFB alleles are identified for peach cultivars and their wild relatives in this study.…”
Section: Discussionmentioning
confidence: 60%
“…More recently, two additional S-haplotypes have been reported (Hanada et al 2014). Whereas, over 20 S-haplotypes are reported in other Prunus species such as almond, sweet cherry, plum, apricot, and Japanese apricot (Ushijima et al 2003(Ushijima et al , 2004Yamane et al 2003a, b;Romero et al 2004;Vaughan et al 2006;Zhang et al 2007;Wu et al 2009Wu et al , 2013. In apple, S-haplotype profiling has been widely used in characterizing apple cultivars (Janssens et al 1995;Bokszczanin et al 2009;Kim et al 2009;Long et al 2010;Minamikawa et al 2010).…”
mentioning
confidence: 99%
“…Primer sequence Reference SRc-R 5'-GGC CAT TGT TGC ACA AAT TG-3' Vilanova et al [25] SRc-F 5'-CTC GCT TTC CTT GTT CTT GC-3' Romero et al [24] Kabaasi and Paviot cultivars were bidirectionally sequenced, BLAST searched in NCBI GenBank and in them, the S-alleles were determined as S 1 S 9 . Apricots belonging to the IranÀCaucasian eco-geographical group have been reported to be mostly selfincompatible, those in the European eco-geographical group, mostly self-compatible and 60% of the varieties in Turkey have been found to be self-incompatible.…”
Section: Primersmentioning
confidence: 99%
“…The S-haplotype contains a female determinant, (S-RNase) encoding for a ribonuclease enzyme (McClure et al 1989), and the recently identified male determinant, S-haplotype-specific F-box gene (Entani et al 2003;Romero et al 2004;Halasz et al 2010). …”
Section: S-genotyping In Genetic Diversity Of Apricotmentioning
confidence: 99%